CD154 Expression Indicates T Cell Activation Following Tetanus Toxoid Vaccination of Horses - Schnabel, Christiane L.; Fletemeyer, Babette; Lübke, Sabrina; Marti, Eliane; Wagner, Bettina; Alber, Gottfried (Frontiers in Immunology, 2022)
Despite the relevance of adaptive immunity against equine pathogens antigen-specific T cell responses of horses are not well characterized and the lack of insight into T cell responses hampers the understanding of the pathogeneses of important diseases. In this study we used tetanus toxoid (TT) as a well-defined antigen to characterize antigen-reactive T cells. Six healthy adult horses received a routine booster against tetanus with an immune stimulating complex (ISCOM)-based vaccine and were followed for 28 days. TT-specific serum antibodies were quantified by ELISA and increased in all horses by day 7 after vaccination. CD154 is an established indicator of antigen-reactive T helper cells in other species, but has not been characterized in horses. CD154 detection in equine PBMC by an anti-human CD154 antibody (clone 5C8) was confirmed by Western blots and then applied for flow cytometry. As a common indicator of equine T cell activation, cytokine induction was studied in parallel. T cells were analyzed by multicolor flow cytometry of PBMC after re-stimulation with TT in vitro. Reactive T helper (Th) cells were characterized by increased frequencies of CD4+CD154+ lymphocytes in in vitro TT-re-stimulated PBMC on day 14 after vaccination of the horses compared to pre-vaccination. The majority of all CD154+ cells after TT re-stimulation were CD4+ Th cells, but CD154 was also induced on CD4- cells albeit in lower frequencies. CD154+CD4+ Th cells were enriched in cytokine-expressing cells compared to CD154-CD4+ Th cells. Similar to the CD4+CD154+ frequencies, CD4+IL-4+, CD4+IFN-γ+ and CD4+TNF-α+ were increased after vaccination, but IL-4+ increased later than IFN-γ+ and CD4+TNF-α+, which already exceeded pre-vaccination frequencies on day 7. CD4+CD154+ frequencies correlated positively with those of CD4+IL-4+ (Th2) on day 14, and negatively with CD4+IFN-γ+ induction on day 7, but did not correlate with CD4+TNF-α+ frequencies or TT-specific antibody concentrations. CD154 appears to be a useful marker of antigen-reactive equine Th cells in combination with cytokine expression. The T cell analyses established here with TT can be applied to other antigens relevant for infections or allergies of horses and in horse models for translational research.